LOCAL CHAPTER OF NEUROLOGICAL SOCIETY ESTABLISHED TO ENHANCE TALENTS OF LOCAL EXPERTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
19 May 2017 The Walter Dandy Neurosurgical Society Malaysian Chapter made history when it was launched recently at Hospital Kuala Lumpur. The renowned neurosurgeon, Professor Saleem Abdulrauf, the President of the Walter Dandy Neurological Society was present for the launching.